Modelagem numérica de sensores plasmônicos SPCE de 3 e 4 camadas usando o COMSOL em ambiente 2D - COSTA, Maikon Sanches da (2021)
Optical sensors based on SPP waves are known as Surface PlasmonResonance - SPR sensors. These photonic devices detect variations in the effective refractive index of a multilayer structure through the interaction of the plasmonic wave excited at the metal dielectric interface with samples of the material to be analyzed on the sensor surface. SPR sensors can be used for detection of chemical and biological species, monitoring of nanoparticles and so on. In this work, the theoretical analysis of an SPR sensor in SPCE configuration with 3 and 4 layers is presented, where the re-emission process of nanoparticles (or analytes) are modeled by infinitesimal dipoles on the sensor surface, in a length of wave λ = 633 nm or in the optical range. COMSOL Multiphysics® Software is used to numerically analyze, by the finite element method, the electromagnetic response of the SPCE sensor equivalent models with 3 and 4 layers in 2D. The analysis in COMSOL uses the finite element method to calculate the near and far fields, where the results are validated through other results obtained by other references. The validation and analysis of the results for the 2D 4-layer sensor is done by comparing with experimental results for a sensor in the Kretschmann configuration. All results obtained had good agreement, proving the effectiveness of the models created in the Software and the electromagnetic reciprocity of the two configurations of SPR sensors.